Using Netscape 2 with your Mac - Heck, Joseph (Que Corp., 1996)
This follow-up to the bestselling Using Netscape provides detailed coverage of Netscape 2 for Macintosh, including support for Java, new integrated e-mail and newsreading features, new support for online purchases with digital IDs, and more. It also offers information about special HTML editing tools in Netscape Navigator 2 Gold.